Authority, religion and man : a philosophical propaedeutic to a secular understanding of authority in the Christian faith, with special reference to Kant, Hegel and Kierkegaard - Giddy, Patrick (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1982.